PENYULUHAN TATALAKSANA DAN PENCEGAHAN OBESITAS PADA ANAK DAN REMAJA - Sulistyowati, Dwi; Suryanti, Suryanti; Rita Benya Adriani (Tahta Media Grup, 2024)
Health development aims to increase awareness, willingness and ability to live healthily for everyone in order to achieve the highest level of public health. Management means structured and interrelated activities that produce output according to needs, so obesity prevention management is a structured program to prevent obesity. The increase in obesity is accompanied by an increase in comorbidities which have the potential to become degenerative diseases in the future, for example coronary heart disease, hypertension, Type 2 DM, etc. The difficulty of managing obesity makes prevention a top priority. The competence of pediatricians in detecting early adiposity rebound and managing immediate treatment with a healthy diet and activity approach needs to be possessed by all pediatricians in Indonesia. The target is to achieve children, adolescents and the community, and health cadres to understand obesity prevention management. Result: After providing assistance in the management and prevention of obesity, the community understands how to carry out and implement the theories regarding obesity prevention that have been given in everyday life.